2011
DOI: 10.1007/s12613-011-0423-z
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Nd and Y additions on the corrosion behaviour of extruded Mg-Zn-Zr alloys

Abstract: To improve the corrosion resistance of wrought magnesium alloys through rare earth (RE) additions, the corrosion behaviour of Mg-5Zn-0.3Zr-xNd (x=0, 1, and 2; wt%) and Mg-5Zn-0.3Zr-2Nd-yY (y=0.5 and 1; wt%) alloys in a 5wt% NaCl solution was investigated using immersion test and electrochemical measurements. The results of immersion test show that Mg-5Zn-0.3Zr-2Nd alloy exhibits the best corrosion resistance among the tested alloys. Electrochemical measurements show that secondary phases in RE-containing Mg-5Z… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 14 publications
(16 reference statements)
1
7
0
Order By: Relevance
“…A decrease in the corrosion rates of Mg alloys alloyed with RE elements was also reported by Nam et al, Liu et al, and Chang et al Nam et al studied the influence of alloying with up to 1 wt% mischmetal (MM; of composition 50 wt% Ce, 25 wt% La, 20 wt% Nd, and 5 wt% Pr) on the corrosion behaviour of Mg–5Al using electrochemical testing in 0.06 wt% NaCl solution, and reported that increasing the MM content in Mg–5Al increased (a) the pitting potential, (b) the charge transfer resistance implying a decreased corrosion rate, and (c) the film resistance. The authors attributed this decrease in corrosion rate to grain size reduction of the α matrix, and the precipitation of a high density of more continuous Al–MM compounds.…”
Section: Introductionsupporting
confidence: 58%
“…A decrease in the corrosion rates of Mg alloys alloyed with RE elements was also reported by Nam et al, Liu et al, and Chang et al Nam et al studied the influence of alloying with up to 1 wt% mischmetal (MM; of composition 50 wt% Ce, 25 wt% La, 20 wt% Nd, and 5 wt% Pr) on the corrosion behaviour of Mg–5Al using electrochemical testing in 0.06 wt% NaCl solution, and reported that increasing the MM content in Mg–5Al increased (a) the pitting potential, (b) the charge transfer resistance implying a decreased corrosion rate, and (c) the film resistance. The authors attributed this decrease in corrosion rate to grain size reduction of the α matrix, and the precipitation of a high density of more continuous Al–MM compounds.…”
Section: Introductionsupporting
confidence: 58%
“…38 In the ZEK100, Zr and Nd together are added as grain refiners with the general claim that Zr has a negative effect on corrosion, while Nd reduces the cathodic activity of the phase which hosts it. 39 In the presence of chloride, both Mg-Zn-Nd and Zr, particles were located in the corroded region with Zr particles containing Fe appearing to be the dominant microgalvanically coupled cathodes. By initiating corrosion in pure water, it was possible to limit the extent of corrosion damage due to microgalvanic coupling to the vicinity of the coupled cathodes.…”
Section: Discussionmentioning
confidence: 98%
“…By optimizing the content of Zn (Mg3Zn0.6Zr, in wt.%) in Mg-Zn-Zr alloy, the corrosion rate of Mg-Zn-Zr alloy can be comparable to that of WE43 alloy, which exhibits good corrosion behavior relative to AZ31, AZ91, and LAE42 alloys [125,127]. The further addition of Y and/or neodymium (Nd) into Mg-Zn-Zr alloys results in the precipitation of less noble T-phase and/or W-phase, and leads to the formation of more a compact corrosion product layer with higher corrosion resistance [128,129]. It is quite often observed for Mg alloys that the protective film is denser when the overall corrosion rate is low.…”
Section: Representative Mg-zn-re and Mg-zn-zr Based Alloysmentioning
confidence: 99%